Coronavirus Disease 19 (COVID-19) Vaccine Effectiveness Against Symptomatic Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) Infection During Delta-Dominant and Omicron-Dominant Periods in Japan: A Multicenter Prospective Case-control Study (Factors Associated with SARS-CoV-2 Infection and the Effectiveness of COVID-19 Vaccines Study). (1st September 2022) - Arashiro, Takeshi; Arima, Yuzo; Muraoka, Hirokazu; Sato, Akihiro; Oba, Kunihiro; Uehara, Yuki; Arioka, Hiroko; Yanai, Hideki; Kuramochi, Jin; Ihara, Genei; Chubachi, Kumi; Yanagisawa, Naoki; et al.
Abstract: Background: Although several coronavirus disease 2019 (COVID-19) vaccines initially showed high efficacy, there have been concerns because of waning immunity and the emergence of variants with immune escape capacity. Methods: A test-negative design case-control study was conducted in 16 healthcare facilities in Japan during the Delta-dominant period (August-September 2021) and the Omicron-dominant period (January-March 2022). Vaccine effectiveness (VE) against symptomatic severe acute respiratory syndrome coronavirus 2 infection was calculated for 2 doses for the Delta-dominant period and 2 or 3 doses for the Omicron-dominant period compared with unvaccinated individuals. Results: The analysis included 5795 individuals with 2595 (44.8%) cases. Among vaccinees, 2242 (55.8%) received BNT162b2 and 1624 (40.4%) received messenger RNA (mRNA)-1273 at manufacturer-recommended intervals. During the Delta-dominant period, VE was 88% (95% confidence interval [CI], 82–93) 14 days to 3 months after dose 2 and 87% (95% CI, 38–97) 3 to 6 months after dose 2. During the Omicron-dominant period, VE was 56% (95% CI, 37–70) 14 days to 3 months since dose 2, 52% (95% CI, 40–62) 3 to 6 months after dose 2, 49% (95% CI, 34–61) 6+ months after dose 2, and 74% (95% CI, 62–83) 14+ days after dose 3. Restricting to individuals at high risk of severe COVID-19 and additional adjustment for preventive measures (ie, mask wearing/high-risk behaviors) yielded similar estimates, respectively. Conclusions: In Japan, where most are infection-naïve, and strict prevention measures are maintained regardless of vaccination status, 2-dose mRNA vaccines provided high protection against symptomatic infection during the Delta-dominant period and moderate protection during the Omicron-dominant period. Among individuals who received an mRNA booster dose, VE recovered to a high level. Abstract : In this test-negative case-control study in Japan, 2-dose messenger RNA (mRNA) coronavirus disease 2019 vaccines provided high and moderate protection against symptomatic infection during the Delta- and Omicron-dominant period, respectively. Among mRNA booster recipients, vaccine effectiveness recovered to a high level in the short-term.